National Dam Safety Program. Pinchot Lake Dam (Inventory Number NDS 335), Susquehanna River Basin, Beaver Creek, York County, Pennsylvania. Phase I Inspection Report. - BERGER ASSOCIATES INC HARRISBURG PA (1978)
The Dam Inspection Act, Public Law 92-367 (Appendix III) authorized the Secretary of the Army, through the Corps of Engineers, to initiate a program of safety inspections of dams throughout the United States. Phase I INSPECTION AND Report is limited to a review of available data, a visual inspection of the dam site and the basic calculations for determining the hydraulic adequacy of the spillway. The purpose is to determine if the dam constitutes a hazard to human life and property.